Critical reflection, unlearning, and engagement. Issue 4 (September 2019) - Matsuo, Makoto
Although individual unlearning is believed to play a critical role in promoting higher-order learning, there has been little quantitative research on this process. This article aimed to investigate the antecedents and consequences of individual unlearning based on transformative learning theory. A survey was conducted among 301 employees working in various occupations and organizations in the United States. The results of structural equation modeling indicated that unlearning mediated the relationship between critical reflection and work engagement and that critical reflection mediated reflection and unlearning. This study contributes to the literature by quantitatively demonstrating the direct and indirect influences of critical reflection on work engagement through individual unlearning, which has been discussed only conceptually and qualitatively in the extant transformative learning literature.